Geographic and Oceanographic Influences on Ferromanganese Crust Composition Along a Pacific Ocean Meridional Transect, 14 N to 14S - Kira Mizell; James R. Hein; Phoebe J. Lam; Anthony A. P. Koppers; Hubert Staudigel (Geochemistry, Geophysics, Geosystems, 2020)
Abstract The major controls on the variability of ferromanganese (FeMn) crust composition have been generally described over the past 40 years; however, most compilation studies lack quantitative statistics and are limited to a small region of several seamounts or compare FeMn crusts from disparate areas of the global oceans. This study provides the first detailed research to address the geographic and oceanographic controls of FeMn crust composition from a line of seamounts across 30° of latitude in the west central Pacific. Element concentrations from the uppermost layer (<15 mm) of 57 FeMn crusts were evaluated for statistically significant variance and correlation with a variety of oceanographic and geographic parameters. Manganese, Co, Ni, Mo, and Zn concentrations in crusts in this region are highly anticorrelated with seawater oxygen concentrations, suggesting oxygen as the dominant controlling factor for these elements. Iron instead correlates with water depth, which we attribute to increased carbonate ion concentration with increasing water depth. Silicon and Al content in crusts demonstrate a potential meridional variance of detrital inputs and sources in the region. Iron, Ba, and Mg are enriched in FeMn crusts below the equatorial upwelling zone which is related to biological productivity. Fluctuations in the four oceanographic and geographic parameters, seawater oxygen content, detrital input, surface productivity, and deep sources of iron, are robustly recorded by FeMn crusts. Modern measurements of these primary parameters, as well as paleoceanographic reconstructions, can be used to define regions of interest for FeMn crust exploration.